2018
DOI: 10.1158/1078-0432.ccr-18-0472
|View full text |Cite
|
Sign up to set email alerts
|

Functions and Mechanisms of Tumor Necrosis Factor-α and Noncoding RNAs in Bone-Invasive Pituitary Adenomas

Abstract: To explore the molecular mechanism and prognosis of bone-invasive pituitary adenomas (BIPA). A total of 274 patients with pituitary adenomas were followed up. Transcriptomic microarrays analysis was performed on 10 pituitary adenomas, including five BIPAs and five non-bone-invasive pituitary adenomas (NBIPA). The targeted molecular markers were validated by qRT-PCR, IHC, ELISA, and osteoclast differentiation. Clinical variable analyses revealed a significant correlation between bone invasion and female sex, la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 48 publications
3
51
2
Order By: Relevance
“…SNHG24, a prominent regulator of the ceRNA network, was found to be closely linked with the process of GnRH secretion and neuroactive ligand-receptor interaction, and exhibited signi cant correlation with KISS1. Reports suggest that the lncRNA SNHG24 can regulate TNF-α expression, and TNF-α and its associated lncRNA SNHG24 represent potential therapeutic targets for bone-invasive pituitary adenomas in the future [39]. Eckstein et al [40] highlighted a strong correlation between GnRH secretion and the risk of prostate cancer, which directly supports our ndings.…”
Section: Discussionsupporting
confidence: 82%
“…SNHG24, a prominent regulator of the ceRNA network, was found to be closely linked with the process of GnRH secretion and neuroactive ligand-receptor interaction, and exhibited signi cant correlation with KISS1. Reports suggest that the lncRNA SNHG24 can regulate TNF-α expression, and TNF-α and its associated lncRNA SNHG24 represent potential therapeutic targets for bone-invasive pituitary adenomas in the future [39]. Eckstein et al [40] highlighted a strong correlation between GnRH secretion and the risk of prostate cancer, which directly supports our ndings.…”
Section: Discussionsupporting
confidence: 82%
“…Unpaired t-test *p < 0.05, **p < 0.01, ***p < 0.001 expression. Zhu et al [22]. found that the expression of miR-410-3p was higher in bone-invasive pituitary adenoma compared to nonbone-invasive pituitary adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…1b, p > 0.05). However, based on analysis of an expression dataset published by Zhu et al [22], miR-410-3p was significantly overexpressed in bone-invasive pituitary adenomas (BIPA) compared to nonbone-invasive pituitary adenomas (NBIPA) (fold change 15.13, p = 0.0031) Fig. 1c.…”
Section: Mir-410-3p Is Upregulated In Invasive Tumors Compared To Nonmentioning
confidence: 99%
“…A study on invasive pituitary tumors identified that the TNFα network—including genes coding for proteins (TNFα, CCL3, CXCL12, and CCL2), microRNAs (miR-181c-5p and miR-454-3p) and lncRNAs (NR_033258 and lncRNA_SNHG24)—is upregulated in bone-invasive pituitary adenomas compared nonbone-invasive counterparts, suggesting that targeting the TNFα pathway may be beneficial for these invasive tumors ( 320 ).…”
Section: Epigenetic Mechanisms Of Tumorigenesismentioning
confidence: 99%